Case Report: Giant sacrococcygeal teratoma in neonates—a report of three cases - Wu Ri Ni, Letu; Nong, Yimin; Wang, Jinben; Liang, Xiujian; Zhang, Baoxin; Lin, Zhenying (Frontiers in Pediatrics, 2025)
Although most cases of neonatal sacrococcygeal teratoma are benign, some can grow into very large lesions, potentially causing high-output heart failure, massive bleeding, disseminated intravascular coagulation, and even fatal outcomes. We report three cases of giant sacrococcygeal teratomas, detailing their diagnostic and therapeutic management. We emphasize that clinicians should be prepared with comprehensive contingency plans and that interdisciplinary collaboration is essential to enhance patient survival rates and minimize potential complications.